Regarding the History of Asian Art Collecting: Tracking Collections of the Tea Traders in Russian Regional Museums - Guseva, Anna V.; Demenova, Viktoria V. (Actual Problems of Theory and History of Art, 2019)
While some research has been carried out on the history of formation of Chinese and Japanese art collections in Saint Petersburg and Moscow, only a few studies explored the formation of Asian art collections of regional museums. While the history of collecting indicates that it was a complex and multilayered process, there are a considerable number of Asian objects that are dated from the pre-revolutionary period. Among a number of different sources one is outstanding —a Tea Road from China to Russia.This study hypothesizes that a significant share of Asian objects that are preserved in collections of Russian museums which are located in towns and cities linked geographically and/or economically to the Tea Road could have originated from the collections of the tea traders and because of this these collections could have similarities in structure and quality of the objects. Basing on a survey conducted in cooperation with the specialists in local museums of Yekaterinburg, Irbit, Irkutsk, Ulan-Ude, and Kyakhta, this research aims to distinguish art objects that went back to the pre-revolutionary collections of the tea traders and to detect their provenance and to identify collectors.
Keywords: Asian art; Chinese art; Irbit; Kyakhta; history of collecting; Russian museums; tea traders; tea road